Legal Risks and Regulatory Frameworks for Artificial Intelligence (Journal of Interdisciplinary Insights, 2024)
The promise of innovation and practical applications of artificial intelligence has garnered significant interest and serves as a new motivator for societal advancement. The ensuing legal ramifications have attracted considerable examination. The legal risks associated with artificial intelligence development can be categorized into three areas: data security vulnerabilities during the training phase, algorithmic bias concerns in the generating phase, and the potential for misuse as illegal or criminal instruments in the application phase. This article employs a thorough research methodology, encompassing a literature review of notable legal cases and laws, alongside case-specific evaluations of particular artificial intelligence applications. Research findings indicate that a comprehensive regulatory framework, which meticulously assesses both the process and the outcome, is essential for mitigating legal risks at every level of artificial intelligence. This framework must encompass data security safeguards, mitigation of algorithmic bias, and explicit delineation of responsibilities. The investigation into the regulatory framework is crucial as it can mitigate legal challenges and foster social advancement by establishing a definitive legal guideline for the progression of artificial intelligence.
Keywords: Artificial Intelligence; Legal Risks; Regulatory Frameworks